Idiopathic Orofacial Granulomatosis with Varied Clinical Presentation - Rathy Ravindran; Anila Karunakaran (Hindawi Limited, 2013)
Orofacial granulomatosis is a granulomatous disease of orofacial region, which can occur for a variety of reasons. The clinical features are highly variable and sometimes so insidious that signs and symptoms are not frequently severe to cause alarm. The lips are most commonly involved with persistent/recurrent swelling. The medical history is very important as Crohn's disease and sarcoidosis can present oral manifestation. Other causes like mycobacterial infection, foreign body reaction, fungal infection, and allergy were excluded with further investigation to establish diagnosis. Here and we report a case of orofacial granulomatosis with a review of the literature.